2021
DOI: 10.1093/noajnl/vdab072
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IL-8 and ICOSLG as prognostic biomarkers in glioblastoma

Abstract: Background CNS immune privilege has been challenged in recent years. Glioblastoma (GBM) immune dysfunction includes complex interactions with the immune system outside the CNS. The aim of this study was to determine diagnostic and prognostic potential of immune-related proteins in plasma in GBM and interrogate biomarker presence in the brain tumor microenvironment (TME). Methods 158 patients with glioma WHO grade II–IV were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
7
2
Order By: Relevance
“…Moreover, EIF4A3 induced the formation of circular RNA ASAP1 ( 49 ) and MMP9 ( 50 ), which both promoted glioblastoma tumorigenesis. In a study investigating immune system-related plasma proteins in glioblastoma ( 51 ), researchers found that high CD244 levels were associated with long progression-free survival, which seems contradictory to our results. An in vitro experiment by Wu et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, EIF4A3 induced the formation of circular RNA ASAP1 ( 49 ) and MMP9 ( 50 ), which both promoted glioblastoma tumorigenesis. In a study investigating immune system-related plasma proteins in glioblastoma ( 51 ), researchers found that high CD244 levels were associated with long progression-free survival, which seems contradictory to our results. An in vitro experiment by Wu et al.…”
Section: Discussioncontrasting
confidence: 99%
“…IL-8 was mostly secreted and expressed by mesenchymal GBM cell lines and expressed by vascular cells and immune cells. High plasma IL-8 at surgery was associated with short OS in newly diagnosed GBM [36].…”
Section: Discussionmentioning
confidence: 92%
“…IL-8 was mostly secreted and expressed by mesenchymal GBM cell lines and expressed by vascular cells and immune cells. High plasma IL-8 at surgery was associated with short OS in newly diagnosed GBM (34).…”
Section: Discussionmentioning
confidence: 92%